The role of tourism in the chinese economy - Tulkunova Xilola; Khikmatov Dilshodjon (Periodica Journal, 2022)
Today tourism is the most developing industry and the best source of income. The author of this article analayzes the developed of tourism in China, the role of tourism in the economy and the benefit to the state budget
Keywords: Tourism; medical tourism; educational tourism